The chromosomal integration site determines the tissue-specific methylation of mouse mammary tumour virus proviral genes. - Günzburg, W H (1984)
Multiple endogenous mouse mammary tumour virus (MMTV) proviral genes are present at different chromosomal locations in inbred mouse strains. Proviral DNA methylation is location and tissue specific. The methylation patterns are stably inherited and appear to be conferred upon the viral DNA by the flanking mouse genomic DNA. In transformed cells, either mammary carcinoma cells, or cells immortalized by SV40 in vitro, the stable pattern of methylation is lost. Although hypomethylation of proviral genes, both in normal and in transformed tissue, accompanies MMTV-specific RNA expression, it is also observed in non-expressing tissues.